Critical voices in school reform : students living through change / edited by Beth C. Rubin and Elena M. Silva. - Rubin, Beth C.; Silva, Elena M. (RoutledgeFalmer, 2003)
This text looks at school reform from the perspective of those most affected by it - the students. This youth centred approach to studying school reforms provides insight into how students experience changes in school structure.